2012
DOI: 10.1525/auk.2012.11164
|View full text |Cite
|
Sign up to set email alerts
|

Demography and dispersal of juvenile and adult Brown-headed Cowbirds (Molothrus ater) in the eastern Sierra Nevada, California, estimated using multistate models

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press and AmericanOrnithologists' Union are collaborating with JSTOR to digitize, preserve and extend access to The Auk.Abstract.-Despite recent progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 86 publications
1
10
1
Order By: Relevance
“…In southern Manitoba, from 1993to 1998, Woolfenden et al (2001) also found the survival probability of adult males greater than that of adult females. Contrasting with our results, and those of Woolfenden et al (2001), in the eastern Sierra Nevada from 1982 to 1988, Anderson et al (2012: figure 3A) estimated the probability of adults' survival to be highest in ASY males (63.4%), lower in females (56.1%) and lowest in SY males (32.9%). Adult female cowbirds may often have shorter lives than adult males because, laying so many eggs in a breeding season, adult females may have difficulty obtaining enough resources to survive this large reproductive effort (Darley 1971).…”
Section: Discussion Age Structurecontrasting
confidence: 99%
See 1 more Smart Citation
“…In southern Manitoba, from 1993to 1998, Woolfenden et al (2001) also found the survival probability of adult males greater than that of adult females. Contrasting with our results, and those of Woolfenden et al (2001), in the eastern Sierra Nevada from 1982 to 1988, Anderson et al (2012: figure 3A) estimated the probability of adults' survival to be highest in ASY males (63.4%), lower in females (56.1%) and lowest in SY males (32.9%). Adult female cowbirds may often have shorter lives than adult males because, laying so many eggs in a breeding season, adult females may have difficulty obtaining enough resources to survive this large reproductive effort (Darley 1971).…”
Section: Discussion Age Structurecontrasting
confidence: 99%
“…Few of the many previous studies of the cowbird (see reviews in Lowther 1993, Ortega, 1998, Morrison et al 1999, and Smith et al 2000, have examined the species' demography during the breeding season (Darley 1971, Woolfenden et al 2001, Ortega and Ortega 2009, Anderson et al 2012, except for the sex ratio (reviewed by Ortega 1998: table 7.2). Especially with respect to the age structure of adult females in a population, this lack of demographic study is surprising since female cowbirds are generally thought to lay typically from 10 to 40 eggs in a breeding season (Walkinshaw 1949, Payne 1965, 1976, Scott and Ankney 1980, Fleischer et al 1987, Holford and Roby 1993, though Alderson et al (1999) esti-mated a mean (± 1 SD) of only 2.8 ± 2.7 eggs laid by a female cowbird in a breeding season.…”
mentioning
confidence: 99%
“…Our estimates of the cowbird dispersal distance are consistent with their predominantly local movements as adults (Anderson et al ., ). Accordingly, cowbird occupancy and density have been related to local factors including host richness, landscape fragmentation and increasing urbanization, but not to climatic factors or other large‐scale environmental gradients (Robinson, ; Chace et al ., ; Cummings & Veech, ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, because cowbirds are good dispersers (Anderson et al, 2005(Anderson et al, , 2012, trapping and removal programs must be implemented each year to have a continuous effect on suppressing cowbird abundance in locations where the species is considered detrimental to other passerines (e.g. For example, because cowbirds are good dispersers (Anderson et al, 2005(Anderson et al, , 2012, trapping and removal programs must be implemented each year to have a continuous effect on suppressing cowbird abundance in locations where the species is considered detrimental to other passerines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cowbirds often use different habitat types for foraging, roosting and breeding (Chace et al, 2005). In addition, individual cowbirds may travel up to 15 km a day between roosting and feeding sites (Curson et al, 2000) and can permanently disperse even greater distances over longer time spans (Anderson et al, 2012). Overall, cowbirds utilize a variety of land cover types (except expansive forest), and their densities can vary between habitats that are similar, indicating that habitat type is not a sole predictor of cowbird occurrence or density (Rothstein & Robinson, 2000).…”
Section: Introductionmentioning
confidence: 99%